Single‐cell RNA sequencing reveals localized tumour ablation and intratumoural immunostimulant delivery potentiate T cell mediated tumour killing. Issue 7 (8th July 2022) - Hoover, Ashley R.; Liu, Kaili; DeVette, Christa I.; Krawic, Jason R.; Medcalf, Alexandra D.; West, Connor L.; Hode, Tomas; Lam, Samuel S.K.; Welm, Alana L.; Sun, Xiao‐Hong; Hildebrand, William H.; Chen, Wei R.
Abstract: Background: Metastatic breast cancer poses great challenge in cancer treatment. N‐dihydrogalactochitosan (GC) is a novel immunoadjuvant that stimulates systemic immune responses when administered intratumourally following local tumour ablation. A combination of photothermal therapy (PTT) and GC, referred to as localized ablative immunotherapy (LAIT), extended animal survival and generates an activated B cell phenotype in MMTV‐PyMT mouse mammary tumour microenvironment (TME). However, how T cell populations respond to LAIT remains to be elucidated. Methods: Using depletion antibodies, we studied the contributions of CD8 + and CD4 + T cells to the therapeutic effect of LAIT. Using single‐cell RNA‐sequencing (scRNAseq), we analysed tumour‐infiltrating T cell heterogeneity and dissected their transcriptomes upon treatments of PTT, GC, and LAIT (PTT+GC). Results: Loss of CD8 + T cells after LAIT abrogated the therapeutic benefits of LAIT. Ten days after treatment, proportions of CD8 + and CD4 + T cells in untreated TME were 19.2% and 23.0%, respectively. Upon LAIT, both proportions were increased to 25.5% and 36.2%, respectively. In particular, LAIT increased the proportions of naïve and memory cells from a resting state to an activated state. LAIT consistently induced the expression of co‐stimulatory molecules, type I IFN responsive genes, and a series of antitumor cytokines, Ifng, Tnf, Il1, and Il17 in CD8 + and CD4 + T cells. LAIT also induced immune checkpoints Pdcd1, Ctla4, and Lag3 expression, consistent with T cell activation. Relevant to clinical translation, LAIT also upregulated genes in CD8 + and CD4 + T cells that positively correlated with extended survival of breast cancer patients. Conclusions: Overall, our results reveal that LAIT prompts immunological remodelling of T cells by inducing broad proinflammatory responses and inhibiting suppressive signalling to drive antitumour immunity. Abstract : LAIT induced a broad proinflammatory response in tumour‐infiltrating T cells. LAIT causes tumour immunogenic cell death (ICD), releasing danger associated molecular patterns (DAMPs) and tumour antigens (TAs). DAMPs and TAs recruit T cells into the tumour microenvironment, and the GC‐induced cytokines drive their differentiation into T helper 1 and 17 (Th1 and Th17) cells and cytotoxic lymphocytes (CTL).